PERILAKU DAN PENGARUH PENDIRI TERHADAP INFORMATIVITAS HARGA SAHAM: PERUSAHAAN PUBLIK KELUARGA DI INDONESIA - Mira Kartika Dewi Djunaedi (JURNAL LENTERA BISNIS, 2023)
This study examines the relationship between founder as controller, age of founder, and dispersion of control on the informativeness of company stock prices. We argue that behavioral heterogeneity exists in family firms that are still majority owned and controlled by the founder. Using unbalanced panel data from 262 observations, first, this research finds support for the hypothesis that there is a convex relationship between founder voting rights and the informativeness of company stock prices. Second, older founders demonstrate more stewardship behavior than younger founders. Finally, high power dispersion in founding family firms creates agency conflicts between family owners that decrease the informativeness of firm stock prices. This finding is consistent with previous family business literature which reports that mixed behavior among family members can influence the informativeness of family company share prices. Keywords: Family Companies, Behavior Of Company Founders, Ownership Of Founders, Age Of Founders, Stock Price Informativeness